Konsep Akal Menurut Muhammad Abduh DanImplikasinya Dalam Pendidikan Islam - Syarif, Aiman, Dr. Mohamad Ali M.Pd (2016)
Muhammad Abduh is one of Muslim reformation figure in Middle East especially in education field. The reformation made by Muhammad Abduh was begun when he studied in Al-Azhar University, Kairo. He thought that education in al-Azhar was not yet to give great contribution to the society in addressing social issues and solving the complex problems at that time. Hence, Muhamamd Abduh felt that reconstruction in education is needed in the University of al-Azhar. The purpose of the research is to know the intelligence conception based on Muhammad Abduh theory and its implication on Islamic education. This research includes in historical research, this type of research aims to reconstruct an event or events that have occurred in the past systematically, accurately, and objectively. The concept which is brought by Muhammad Abduh emphasized on the intelligence in teaching and learning process. In the definition, intelligence is league from three substance namely the brain, sense, and heart. Intelligence means understand, so that the students who use their intelligence will be easier to understand the materials in their learning process. The result of the study showed that Muhammad Abduh offer a renewal in Islam education that by using intelligent, people will more easily understand in learning process and will be delivered to be the brilliant thinker.